Cannabis Use Disorder Among First-Year Undergraduate Students in Gaborone, Botswana - Anthony A Olashore; Philip R Opondo; John A Ogunjumo; James O Ayugi (SAGE Publishing, 2020)
Cannabis use disorder (CUD) poses major clinical and public health concerns globally. It is a growing problem among the youth in Botswana, yet little research has been done on this subject. The present study hoped to address this gap in knowledge by determining the prevalence and associated factors of CUD among first-year university students in Botswana. A cross-sectional study was conducted among 410 first-year university undergraduates, using a modified version of the 37-item World Health Organization (WHO) drug questionnaire and DSM-5 criteria for CUD. The mean age of the respondents was 20.8 (SD = 1.5) years, and the male to female ratio was 1:1.1. Of the 401 students whose responses were analyzed, 37(9,2%) had used cannabis at least once in the last 12 months, but only 19 (4.7%) met the DSM-5 criteria for CUD. After binary regression analysis, difficulty in coping with the new environment/academic activities, receiving more than 150 USD monthly were positively associated with CUD, while regular participation in religious activities was negatively associated. CUD was found among the first-year undergraduates studied. Promoting protective activities such as religious activities and strengthening programs that teach students how to cope with academic stress and a new environment would be helpful.